Good night, my friends, can you help me with these exercise?

Let $N$ a $k$-manifold, $X$ a compact $(k+1)$-manifold in $\mathbb R^N$, and
$F:X\rightarrow N$ a differentiable map. Let $y\in \operatorname{Reg}(F)\cap \operatorname{Reg}(F|_{\partial X})$
and let $J$ a connected component of $F^{-1}$. Suppose $\partial J\neq\emptyset$, fix a
diffeomorphism $c:[0,1]\rightarrow J$, choose a base $\{w_1,\ldots,w_k\}$ de $T_yN$ and let
$t_0\in[0,1]$ arbitrary. Fixe $h:U\rightarrow h(U)$ a local parametrization of $X$
in $c(t_0)$ and denote by $\langle \cdot,\cdot \rangle$ the usual inner product of $\mathbb R^N$.

Consider $\Phi:c^{-1}(U)\times \mathbb R^{k+1}\rightarrow T_yN\times\mathbb R$ defined by
$$\Phi(t,u)=(d(F\circ h)_{h^{-1}\circ c(t)}\cdot u,\langle dh_{h^{-1}\circ c(t)},c'(t) \rangle).$$

Show that $(w,0)\in \operatorname{Reg}(\Phi)\cap \operatorname{Reg}(\Phi|_{\partial (c^{-1}(U)\times \mathbb R^{k+1})})$
for all $w\in T_yN$.

Thank you
--------
This is what I have done
Let $p\in h^{-1}(h(U)\cap J)$, i.e., $h(p)=c(t)$, or $p=h^{-1}(c(t))$, onde $t\in[0,1]$, then
if $\Phi=(\Phi_1,\ldots\Phi_k,\Phi_{k+1})$
from the definition of $\Phi$ we have that
$$d(F\circ h)_p(u)=(\Phi_1(t,u),\ldots\Phi_k(t,u) )$$
and
$$\left<{dh_p(u),c'(t)}\right>=\Phi_{k+1}(t,u).$$
Now, let $(V,\psi)$ be a parametrization of $F(c_{t_0})$, tal que $F(U)\subset V$. Then
$$d(F\circ h)_p=d(g^{-1}\circ F\circ h)_p.$$

Let $\phi:=g^{-1}\circ F\circ h$, $u=(u_1,\ldots,u_{k+1})\in R^{k+1}$.

$$\begin{array}{l l l}
d(F\circ h)_p(u)&=&\left[
\begin{array}{ccc}
\cfrac{\partial \phi_1}{\partial x_1}(p)
&\cdots&
\cfrac{\partial \phi_1}{\partial x_{k+1}}(p)
\\
\vdots & \dots & \vdots \\
\cfrac{\partial \phi_k}{\partial x_1}(p)
&\cdots&
\cfrac{\partial \phi_k}{\partial x_{k+1}}(p)
\end{array}
\right]\left[
\begin{array}{c}
u_1\\
\vdots \\
\vdots \\
. \\
u_{k+1}
\end{array}
\right]\\
& &\\
&=&\left[
\begin{array}{c}
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial \phi_1}{\partial x_i}(p)\\
\vdots \\
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial \phi_k}{\partial x_i}(p)\\
\end{array}
\right]_{k\times{1}}
\end{array}$$

By definition we have
$$\cfrac{\partial F_l }{\partial x_i}(h(p))=\cfrac{\partial \phi_l}{\partial x_i}(p),l=1,\ldots,k.$$

Hence

$$d(F\circ h)_p(u)=\left[
\begin{array}{c}
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial F_1}{\partial x_i}(h(p))\\
\vdots \\
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial F_k}{\partial x_i}(h(p))\\
\end{array}
\right].$$

Next, let $(W,r)$ be another parametrization of $c(t_0)$, so
$$dh_p=d(r^{-1}\circ h)_p.$$

Denoting $\psi=r^{-1}\circ h$,

$$\begin{array}{l l l}
dh_p(u)&=&\left[
\begin{array}{ccc}
\cfrac{\partial \psi_1}{\partial x_1}(p)
&\cdots&
\cfrac{\partial \psi_1}{\partial x_{k+1}}(p)
\\
\vdots & \dots & \vdots \\
\cfrac{\partial \psi_{k+1}}{\partial x_1}(p)
&\cdots&
\cfrac{\partial \psi_{k+1}}{\partial x_{k+1}}(p)
\end{array}
\right]\left[
\begin{array}{c}
u_1\\
\vdots \\
\vdots \\
. \\
u_{k+1}
\end{array}
\right]\\
& &\\
&=&\left[
\begin{array}{c}
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial \psi_1}{\partial x_i}(p)\\
\vdots \\
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial \psi_{k+1}}{\partial x_i}(p)\\
\end{array}
\right]_{(k+1)\times{1}}
\end{array}$$

In the same way we get
$$\cfrac{\partial h_l }{\partial x_i}(p)=\cfrac{\partial \psi_l}{\partial x_i}(p),l=1,\ldots,k.$$

Then

$$dh_p(u)=\left[
\begin{array}{c}
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial h_1}{\partial x_i}(p)\\
\vdots \\
\displaystyle\sum_{i=1}^{k+1}u_i\cfrac{\partial h_{k+1}}{\partial x_i}(p)\\
\end{array}
\right].$$

As $c'(t)=(c_1'(t),\ldots,c_{k+1}'(t))$, we have
$$\left<{dh_p(u),c'(t)}\right>=\Phi_{k+1}(t,u)=\di splaystyle\sum_{i,j=1}^{k+1}\cfrac{\partial h_j}{\partial x_i}(p)u_i\cdot c_j'(t).$$
hence

$$\begin{array}{l l l}
\Phi_l(t,u)&=&\displaystyle\sum_{i=1}^{k+1}u_i \cfrac{\partial F_l}{\partial x_i}(h(p)),\qquad l=1,\ldots,k.\\
& & \\
\Phi_{k+1}(t,u)&=&\displaystyle\sum_{i,j=1}^{k+1}u _i\cfrac{\partial h_j}{\partial x_i}(p)\cdot c_j'(t) \end{array}.$$

Then
$$\cfrac{\partial \Phi_l}{\partial u_j}(t,u)=\cfrac{\partial F_l}{\partial x_j}(h(p)),\qquad \mbox{ for }l=1,\ldots,k,j=1,\ldots,k+1,$$

hence

$$\left[\cfrac{\partial\Phi_l}{\partial u_j}(t,u)\right]_{1\leq j\leq k+1,\\ 1\leq l\leq k}=\left[\cfrac{\partial F_l}{\partial x_j}(h(p))\right]_{1\leq j\leq k+1,\\ 1\leq l\leq k}=dF_{c(t)}.$$

And also for $i=1,\ldots,k+1$
$$\cfrac{\partial\Phi_{k+1}}{\partial u_i}(t,u)=\displaystyle\sum_{j=1}^{k+1}\cfrac{\par tial h_j}{\partial x_i}(p)\cdot c_j'(t)=\left(\cfrac{\partial h_1}{\partial x_i}(p),\ldots,\cfrac{\partial h_{k+1}}{\partial x_i}(p)\right)\cdot c'(t).$$

As
$$dh_p=\left[
\begin{array}{ccc}
\cfrac{\partial h_1}{\partial x_1}(p)
&\cdots&
\cfrac{\partial h_1}{\partial x_{k+1}}(p)
\\
\vdots & \dots & \vdots \\
\cfrac{\partial h_{k+1}}{\partial x_1}(p)
&\cdots&
\cfrac{\partial h_{k+1}}{\partial x_{k+1}}(p)
\end{array}
\right],$$

then

$$(dh_p)^t=\left[
\begin{array}{ccc}
\cfrac{\partial h_1}{\partial x_1}(p)
&\cdots&
\cfrac{\partial h_{k+1}}{\partial x_{1}}(p)
\\
\vdots & \dots & \vdots \\
\cfrac{\partial h_{1}}{\partial x_{k+1}}(p)
&\cdots&
\cfrac{\partial h_{k+1}}{\partial x_{k+1}}(p)
\end{array}
\right],$$

so

$$\begin{array}{l l l}
(dh_p)^t(c'(t))&=&\left[
\begin{array}{ccc}
\cfrac{\partial h_1}{\partial x_1}(p)
&\cdots&
\cfrac{\partial h_{k+1}}{\partial x_{1}}(p)
\\
\vdots & \dots & \vdots \\
\cfrac{\partial h_{1}}{\partial x_{k+1}}(p)
&\cdots&
\cfrac{\partial h_{k+1}}{\partial x_{k+1}}(p)
\end{array}
\right]\left[
\begin{array}{c}
c'_1(t)\\
\vdots \\
\vdots \\
. \\
c'_{k+1}(t)
\end{array}
\right]\\
& &\\
&=&\left[
\begin{array}{c}
\cfrac{\partial\Phi_{k+1}}{\partial u_1}(t,u)\\
\vdots \\
\cfrac{\partial\Phi_{k+1}}{\partial u_{k+1}}(t,u)
\end{array}
\right]
\end{array}.$$

Hence, we get that if

$$z=\left(\cfrac{\partial\Phi_{k+1}}{\partial u_1}(t,u),\dots,
\cfrac{\partial\Phi_{k+1}}{\partial u_{k+1}}(t,u)\right),$$


$z\in Im((dh_p)^t)$ and. Now, if $(u,t)\in\Phi^{-1}(w,0)$ i do not how to use what i have gotten.